The Northern Ireland trade union movement - Bleakley, D. W. (Statistical and Social Inquiry Society of Ireland, 1954)
Twenty-eight years ago, this Society listened to a paper on Irish trade unionism. Then, the speaker outlined a movement that was trying to adjust itself to vital political changes that had taken place in the life of the country in the previous few years. Tonight, though we narrow our range to Northern Ireland, we will be examining a movement which is once again going through a period of fundamental adjustment. It will be my task to outline the movement to you; to show how it carries on its work; and to consider some of the problems which concern the unions in this region.
Read before the Society in Belfast, 14th May, 1954
Keywords: Trade unions, Northern Ireland; Northern Ireland, Trade union movement; Labour relations, Northern Ireland; 314.15